Comparative suitability of two culture media to the in vitro growth of embryos of three coconut types - Nuñez, Tessie C. (Annals of Tropical Research, 2007)
Using a suitable medium for specific plant genotype greatly improves the efficiency of the in vitro culture method. The Visayas State University (VSU)-based National Coconut Research Center-Visayas (NCRC-V) evaluated the comparative suitability of the COGENT medium and VSU-modified Y3 (mY3) as in vitro culture media for coconut embryos using Albuera Dwarf (ALD), Baybay Tall (BAYT), and the VSU-developed Coconiño x Macapuno (VMAC1) hybrid. These two media differ in vitamin components, iron concentration and state during the first two stages of culture, namely germination and first subculture. Results showed that mY3 was more suitable for the in vitro germination and development of the coconut embryos than the COGENT medium. Significantly higher germination rates were observed in BAYT, ALD, and VMAC1 cultured in the semi-solid mY3 than those in the liquid COGENT medium from the first week until the fourth week of initial culture. Germination rates of 100%, 85.8% and 84.5% were obtained from CÑO x MAC, ALD, and BAYT, respectively. Furthermore, significantly higher percentages of germinating embryos with developing shoot and root were observed in the semi-solid mY3 than in the liquid COGENT. Likewise, better growth of plantlets in liquid mY3 was noted during the fourth and fifth months of culture. Among coconut types. VMAC1 has the highest germination rates in the two media and the best growth in mY3. BAYT had better growth in the COGENT medium while ALD has better shoot development in mY3.